Intradiaphragmatic extralobar pulmonary sequestration: A rare anomaly - K. Crowley; H. Stalewski; D. Carroll; B. Mariyappa-Rathnamma (Elsevier, 2022)
We present a case of intradiaphragmatic extralobar pulmonary sequestration (IDEPS) prenatally diagnosed via ultrasound and MRI. Originally seen in the second trimester, the lesion was followed with serial imaging pre and postnatally until being resected thorascopically at 2 years of age.